Do Management Practices Matter in Further Education? - Sandra McNally; Luis Schmidt; Anna Valero (Institute of Labor Economics (IZA), 2022)
Further Education colleges are a key way in which 16-19 year olds acquire skills in the UK (much like US Community Colleges), especially those from low income backgrounds. Yet, little is known about what could improve performance in these institutions. We design and conduct the world's first management practices survey in these colleges (based on the World Management Survey) and match this to administrative longitudinal data on over 40,000 students. Value added regressions with rich controls suggest that structured management matters for educational outcomes (e.g. upper secondary qualifications), especially for students from low-income backgrounds. In a hypothetical scenario where a learner is moved from a college at the 10th percentile of management practices to the 90th, this would be associated with 8% higher probability of achieving a good high school qualification, which is nearly half of the educational gap between those from poor and non-poor backgrounds. Hence, improving management practices may be an important channel for reducing inequalities.
Keywords: I20; J24; 330; management practices; further education